Inhibition of free nitrous acid and free ammonia on polyphosphate accumulating organisms: Evidence of insufficient phosphorus removal through nitritation-denitritation. (1st November 2021) - Andreadakis, Dimitris; Noutsopoulos, Constantinos; Fragkiskatos, Gerasimos; Mamais, Daniel; Misirli, Theodora; Argyropoulou, Kyriaki; Themeli, Eva; Malamis, Simos
Abstract: The purpose of this study is to investigate the effect of Free Nitrous Acid (FNA) and Free Ammonia (FA) on enhanced biological phosphorus removal (EBPR) and in particular on the aerobic phosphorus uptake rate (PUR). To this end, a PAO-enriched biomass was developed at a lab-scale reactor in order to fuel a series of ex-situ batch experiments to test the effect of various nitrite or ammonium concentrations on the phosphorus uptake rate at different pH values. FNA was found to be a strong inhibitor of EBPR, in agreement with other studies with PUR being inhibited by 50 % under 1.5 μg HNO2 –N L −1 and 100 % at 13 μg HNO2 –N L −1 . FA was also found to inhibit EBPR with PUR being inhibited by 50 % under 6.4 mg NH3 –N L −1 . The results of this study suggest that EBPR under high nitrogen loading alongside nitritation-denitritation may not be a viable option. Graphical abstract: Image 1 Highlights: Free nitrous acid strongly inhibits polyphosphate accumulating organisms. Free nitrous acid inhibition is best described by a non-competitive model. Free ammonia is found to inhibit polyphosphate accumulating organisms. Free ammonia inhibition is best described by an uncompetitive model. Biological phosphorus removal under nitritation-denitritation is challenging.